2014
DOI: 10.1038/jhh.2014.71
|View full text |Cite
|
Sign up to set email alerts
|

Large artery stiffness and carotid intima-media thickness in relation to markers of calcium and bone mineral metabolism in African women older than 46 years

Abstract: Vascular calcification and cardiovascular diseases have been associated with altered bone metabolism. We explored the relationships of arterial pressures and carotid intima-media thickness (CIMT) with parathyroid hormone, 25-hydroxycholecalciferol and their ratio (PTH:25(OH)D3) as well as a marker of bone resorption (CTX) in lean and overweight/obese African women. A population of 434 African women older than 46 years was divided into lean and overweight/obese groups. We assessed brachial blood pressure, centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Li [ 50 ] hypothesized that vitamin D could have an influence on the renin–angiotensin system (RAS), which was substantiated by a study that reported how low concentrations of 25(OH)D upregulated the RAS [ 51 ]. In our population, 25(OH)D was reported to be associated with carotid wall thickening and arterial stiffness [ 52 ], both being attributes observed in individuals with increased CRP concentrations. This is a possible mechanism whereby low 25(OH)D could result in increased arterial stiffness, and in turn result in increased blood pressure [ 53 ], leading to elevated CRP concentration by negative feedback mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Li [ 50 ] hypothesized that vitamin D could have an influence on the renin–angiotensin system (RAS), which was substantiated by a study that reported how low concentrations of 25(OH)D upregulated the RAS [ 51 ]. In our population, 25(OH)D was reported to be associated with carotid wall thickening and arterial stiffness [ 52 ], both being attributes observed in individuals with increased CRP concentrations. This is a possible mechanism whereby low 25(OH)D could result in increased arterial stiffness, and in turn result in increased blood pressure [ 53 ], leading to elevated CRP concentration by negative feedback mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that patients with vascular calcification "have lower lumbar spine and hip BMD and increased risk for developing osteoporosis or osteopenia". Whilst it is possible that aspects of increased vascular calcification may contribute to declines in bone density (through common risk factors such as age, smoking, low levels of physical activity and chronic inflammation), this conclusion potentially ignores evidence that vascular calcification can also result from dysregulated bone metabolism in ageing [2][3][4].…”
Section: To the Editormentioning
confidence: 99%